The Loss Aversion Effect in Blind Box Purchases: Why Are Consumers More Willing to Make Additional Purchases? - Xiaoyu Feng (Studies in Social Science & Humanities, 2025)
This paper investigates the loss aversion effect in blind box purchases and why consumers are more willing to make additional purchases within the Chinese market context. By examining psychological principles such as loss aversion, fear of missing out (FOMO), and the Zeigarnik Effect, the study explores how these factors interact with the unique mechanics of blind box marketing. The influence of randomness, rarity, and collectability is analyzed to understand how consumer behavior is shaped by emotional triggers and cognitive biases. Marketing strategies employed by companies to leverage loss aversion, including limited editions, countdown promotions, and reward systems, are discussed in detail. Furthermore, the study highlights the paradox of consumer satisfaction, where disappointment does not necessarily reduce consumption due to post-purchase rationalization and cognitive dissonance. Future implications are considered, including ethical concerns about the exploitation of psychological principles and the potential for stricter regulations. The findings suggest that companies need to balance profitability with ethical responsibility to sustain long-term growth in the blind box market.